Os impostos e a religi??o: a imunidade dos templos de qualquer culto no ordenamento jur??dico brasileiro sob a ??tica do Supremo Tribunal Federal - Oliveira, Ricardo Lima de (2016)
Religion and tributes have always gone together throughout the history of mankind. Religiousness is a remarkable feature of a great part of the world's population. Therefore, the immunity of the temples of any worship is an issue that arouses the interest of the legal community, presenting controversies, and generating diverse considerations, fomented, in particular, by the recent broadening intelligence adopted by the Federal Supreme Court regarding the concept of the expression ???Temples of any worship servisse??? contemplated in the Brazilian Federal Constitution of 1988, on its article 150, VI," b ". The concepts of "worship" and "temple" are not settled in the national legislation, and it is up to the doctrine and jurisprudence to define them. The secularisation of the State and the tributary immunity over the temples of any worship service raise questions about the constitutional interpretation historically given to the issue and enable of variances over the original intention of mentioned immunity. The main purpose of this study is to answer if the tributary immunity, effectively guarantees the right of freedom of belief of Brazilian citizens is.